Is Working from Home Good Work or Bad Work? Evidence from Australian Employees - Dockery, Alfred Michael; Bawa, Sherry (The Centre for Labour Market Research, Curtin Business School, Curtin University of Technology, 2014)
There is concern that workers are finding it increasingly difficult to balance work and family life and face growing time stress. Working from home is one form of flexibility in working arrangements that may assist workers to juggle work and non-work commitments. However, it may also provide a pathway for greater intrusion of work into family life and for added work-related stress. Data from the Household, Income and Labour Dynamics in Australia Survey indicates that around 17 per cent of Australian employees work some of their usual working hours from home, but there has been no increase in the incidence of employees working from home in the past decade. Overall, the ability to work some hours from home is seen by employees as a positive job attribute that provides flexibility to balance work and non-work commitments. However, working from home is also associated with long hours of work and the evidence provides grounds for concern that working from home does facilitate greater intrusion into non-work domains of life through this channel.